The Effect Between Transverse Abdominis Plane Block And Quadratus Lumborum Block On Endorphin Beta Levels And Pain Scales In Post Cesarean Section Patients - Rudyanto Wiharjo Seger; Christrijogo Sumartono; Puspa Wardhani; Aditiawarman Aditiawarman (JURNAL WIDYA MEDIKA, 2020)
Background: Cesarean section is a surgical procedure that is often performed in labor and causes moderate to severe pain for 48 hours postoperatively. The provision of local anesthesia drugs post-cesarean section can be given by the Transverse Abdominis Plane (TAP) block and Quadratus Lumborum (QL) block. This study was to determine the effect of analgesia between the Transverse Abdominis Plane block and Quadratus Lumborum block on the scale of post-cesarean section pain and level of the beta-endorphin post-operative cesarean section under spinal anesthesia. Methods: An experimental randomized controlled clinical trial study was conducted on 30 pregnant women aged 18-45 years post-cesarean section who were treated electively with ASA I - II and anesthesia under spinal anesthesia. Patients who met the inclusion criteria were treated by dividing three groups randomly through the computer. In group A, control and Transverse Abdominis Plane Block are given; group B, given control and Quadratus Lumborum Block; and group C, given control (ketorolac and tramadol). Furthermore, it was recorded and measured the level of beta-endorphin, and the Wong Baker Faces Scale (WBFS) pain scale postoperatively and 6 hours postoperatively. Data collected then analyzed by SPSS’s computer program. Results: The effect of QL block administration helps relieve the WBFS pain scale by five times and decreases beta-endorphin level by 0.2 times compared to TAP block administration. The effect of QL block administration helped relieve the WBFS pain scale by 13.5 times and decreased beta-endorphin level by 5.4 times compared to standard therapy. The effect of TAP block administration helps to reduce the WBFS pain scale by 7.4 times and to reduce beta-endorphin level by 5.1 times compared to standard therapy. Conclusion: QL block relieves the WBFS pain scale and decreases the beta-endorphin level better than the TAP block. Keywords: Cesarean section, post-operative pain, beta-endorphin, Quadratus Lumborum block, Transversus Abdominis Plane block